IWork '08 - Harrington, Richard, 1972- (Apple training series., 2008)
IWork 08 Keynote, Pages, Numbers Apple's enhanced iWork productivity suite is poised to allow Mac users to create, present, and publish their work with style. iWork '08 offers three powerful applications--Pages '08, Keynote '08, and the brand-new spreadsheet program, Numbers '08--for creating everything from newsletters and stationery to polished business presentations to graphics-rich spreadsheets. This self-paced learning guide, which includes a companion CD jam-packed with practical media files, takes readers step-by-step through essential, real-life tasks for home and office that cover all aspects of iWork '08. The book is both a self-paced learning tool and the official curriculum of the Apple Training and Certification Program, used by schools and training centers worldwide, and is ideal for users of all levels.